Application of Profile Matching in Selection of the Best Marketing at PT. Dinara Semesta Propertindo - Damiri, Delianto; Prihatin, Titin (SAN Scientific, 2023)
Human resources are a major factor that has an important role in realizing the goals of a company. Regarding the company, it is therefore necessary in a company with the best employee ratings to spur employee morale in improving their performance, so that all activities related to the company continue to move and develop properly. The instrument used in this study which functions as a data collection tool is in the form of a questionnaire using a Likert scale. In determining the best employee research, researchers used samples taken from the marketing population at PT. Dinara Semesta Propertindo, a total of 34 marketing people. The results of the research using the profile matching method based on the ranking above which is the final stage in determining the best marketing using the profile matching method. So the conclusions that can be drawn from this research are the Profile Matching Method can be used as an alternative, a decision support system in determining the best marketing. The stages in using this method include determining the GAP, GAP Weight Value, Grouping Core Factor and Secondary Factor, Total Value, and finally Ranking Determination. Determining the standard value of each aspect or criterion is very influential in the process of determining the best marketing. Sumber daya manusia merupakan suatu faktor utama yang mempunyai peran penting dalam merealisasikan tujuan dari suatu perusahaan. Mengenani perusahaan, Oleh karena itu diperlukan dalam suatu perusahaan dengan adanya penilaian karyawan terbaik untuk memacu semangat kerja para pergawai dalam meningkatkan kinerjanya, agar segala kegiatan yang berkaiatan dengan perusahaan terus bergerak dan berkembang dengan baik. Instrumen yang digunakan pada penelitian ini yang berfungsi sebagai alat pengumpul data adalah berbentuk kuesioner dengan menggunakan skala likert. Dalam penelitian penentuan karyawan terbaik ini, peneliti menggunakan sampel yang diambil dari populasi marketing pada PT. Dinara Semesta Propertindo yang berjumlah 34 orang marketing. Hasil dari penelitian menggunakan metode profile matching berdasarkan dari perangkingan diatas yang merupakan tahap terakhir dalam pemilihan marketing terbaik menggunakan metode profile matching. Maka Kesimpulan yang dapat diambil dari penelitian ini Metode Profile Matching dapat digunakan sebagai alternatif, sistem pendukung keputusan dalam menetukan marketing terbaik, Tahapan dalam menggunakan metode ini meliputi, menentukan GAP, Nilai Bobot GAP, Pengelompokan Core Factor dan Secondary Factor, Nilai Total, dan terakhir Penentuan Ranking. Penentuan standar nilai dari setiap aspek atau kriteria sangat berpengaruh dalam proses penentuan marketing terbaik.